The Influence Of Esg Disclosure On Firm Value With Firm Growth As A Moderator - Dini Kartikasari; Gugus Irianto (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
Increasing investor demands for transparency have made ESG disclosure a strategic element that can maximize firm value. This study aims to assess the influence of ESG disclosure on firm value with firm growth as a moderator. From a population of manufacturing companies listed on the Indonesia Stock Exchange during the 2021-2023 period, 84 were selected as the sample via a purposive sampling technique. The dependent variable of company value is measured using Tobin's Q, the independent variable of ESG is measured through standard GRI content analysis (scale of 0-3), and the moderating variable of company growth is measured using sales growth. The acquired data was analyzed using the Moderated Regression Analysis (MRA). This study finds that ESG disclosure does not significantly influence firm value, indicating that the market tends to perceive that the ESG implementation and disclosure costs are beyond the produced benefits and that the current disclosure quality is not relevant. Further, this study identifies that firm growth significantly moderates the influence of ESG disclosure on firm value. In fast growing com-panies, ESG disclosure is related to firm value increase. This finding demonstrates that investors see ESG transparency as a positive signal from responsible and long-term-oriented management, particularly in companies with sound growth prospects.